Síndrome de burnout: estudo com enfermeiros de um Serviço de Atendimento Móvel de Urgência - Morais, Jocerlania Maria Dias de (2018)
Introduction: The Burnout syndrome (BS) is a process that develops over the years and is hardly noticed in its early stages. Its development is slow, rarely acute and its onset is marked by a physical or mental sensation of undefined malaise and by the presence of an excessive and prolonged level of tension. Objectives: To identify Burnout syndrome in nurses working in a Mobile Emergency Care Service (SAMU); To verify the association of Burnout syndrome with socio-demographic factors and working conditions in nurses who work in the service; To characterize the prevalence of BS and its four dimensions (Illusion for work, psychic waste, indolence and guilt) among nurses working in the service. Methodology: This is a research, descriptive exploratory type, with a quantitative approach. The research was carried out in the six service bases of the city of João Pessoa, Brazil. The studied population consisted of 43 nurses who were part of the Mobile Emergency Care Service (SAMU). Data were collected from August 01 to 30, 2016 and from 01 to 30 in April 2017. The sociodemographic data were analyzed statistically for the identification of burnout syndrome or SQT, direct scores were calculated (DS) for each subscale (obtained by the sum of the Likert scale responses and then divided by the number corresponding to the total questions in that dimension) and another score for the total SQT. The ethical and legal aspects of the research involving human beings, as recommended by Resolution No. 466/12 of the National Health Council, were respected. Results: The majority were women 27 (62.8%), single 17 (39.5%), with children 24 (55.8%), postgraduate 26 (60.5%), and remuneration of up to three minimum wages 25 (58.1%), minimum wages 15 (34.9%). It was verified that the average level of burnout has the highest score 32%, in relation to the other levels, and a critical level of burnout at 5%, with a lower percentage (n = 5) of the participants, two were classified as Profile 1 and three of the participants were classified as Profile. It is observed that only 12% of the respondents presented symptoms of BS. On the other hand, 88% of the sampled population had negative characteristics related to this Syndrome. Conclusion: BS establishes a problem among the nurses who work in SAMU, and interferes in the quality of life of these professionals. It is recommended to rethink the organization of the work of these professionals with a view to preventing this phenomenon that can affect the physical, mental and social health of individuals, with negative consequences for the work process.